Screening for iron deficiency in surgical patients based on noninvasive zinc protoporphyrin measurements. Issue 1 (11th November 2019) - Füllenbach, Christoph; Stein, Philipp; Glaser, Patricia; Triphaus, Chris; Lindau, Simone; Choorapoikayil, Suma; Schmitt, Elke; Zacharowski, Kai; Hintereder, Gudrun; Hennig, Georg; Homann, Christian; Stepp, Herbert; et al.
Abstract : BACKGROUND: Approximately every third surgical patient is anemic. The most common form, iron deficiency anemia, results from persisting iron‐deficient erythropoiesis (IDE). Zinc protoporphyrin (ZnPP) is a promising parameter for diagnosing IDE, hitherto requiring blood drawing and laboratory workup. STUDY DESIGN AND METHODS: Noninvasive ZnPP (ZnPP‐NI) measurements are compared to ZnPP reference determination of the ZnPP/heme ratio by high‐performance liquid chromatography (ZnPP‐HPLC) and the analytical performance in detecting IDE is evaluated against traditional iron status parameters (ferritin, transferrin saturation [TSAT], soluble transferrin receptor–ferritin index [sTfR‐F], soluble transferrin receptor [sTfR]), likewise measured in blood. The study was conducted at the University Hospitals of Frankfurt and Zurich. RESULTS: Limits of agreement between ZnPP‐NI and ZnPP‐HPLC measurements for 584 cardiac and noncardiac surgical patients equaled 19.7 μmol/mol heme (95% confidence interval, 18.0–21.3; acceptance criteria, 23.2 μmol/mol heme; absolute bias, 0 μmol/mol heme). Analytical performance for detecting IDE (inferred from area under the curve receiver operating characteristics) of parameters measured in blood was: ZnPP‐HPLC (0.95), sTfR (0.92), sTfR‐F (0.89), TSAT (0.87), and ferritin (0.67). Noninvasively measured ZnPP‐NI yielded results of 0.90. CONCLUSION: ZnPP‐NI appears well suited for an initial IDE screening, informing on the state of erythropoiesis at the point of care without blood drawing and laboratory analysis. Comparison with a multiparameter IDE test revealed that ZnPP‐NI values of 40 μmol/mol heme or less allows exclusion of IDE, whereas for 65 μmol/mol heme or greater, IDE is very likely if other causes of increased values are excluded. In these cases (77% of our patients) ZnPP‐NI may suffice for a diagnosis, while values in between require analyses of additional iron status parameters.